2002
DOI: 10.1191/0969733002ne507oa
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Reasoning Observed: a longitudinal study of nursing students

Abstract: All nursing courses in the UK include ethics in the curriculum, although there is considerable variation in the content of ethics courses and the teaching methods used to assist the acquisition of ethical reasoning.The effectiveness of ethics courses continues to be disputed, even when the perceptions and needs of students are taken into account in their design. This longitudinal study, carried out in the UK, but with implications for nurse education in other developed countries, explored the ethical understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 22 publications
3
66
1
2
Order By: Relevance
“…Other nursing programs embed the content throughout all courses in the curriculum, and some include instruction on ethical principles only if situations are encountered during a clinical practicum. Whether or not nursing students are adequately prepared to make ethical decisions at the time of graduation is not clear (Dierckx de Casterlé, Grypodonck, Vuylsteke-Wauters, & Janssen, 1997; Krawczyk, 1997;Nolan & Markert, 2002). The ability to make decisions that are ethically based is often learned through practice; consequently, students who were fortunate to encounter ethical situations through their clinical practicum would have an advantage over students who did not.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Other nursing programs embed the content throughout all courses in the curriculum, and some include instruction on ethical principles only if situations are encountered during a clinical practicum. Whether or not nursing students are adequately prepared to make ethical decisions at the time of graduation is not clear (Dierckx de Casterlé, Grypodonck, Vuylsteke-Wauters, & Janssen, 1997; Krawczyk, 1997;Nolan & Markert, 2002). The ability to make decisions that are ethically based is often learned through practice; consequently, students who were fortunate to encounter ethical situations through their clinical practicum would have an advantage over students who did not.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Callister, Luthy, Thompson, and Memmott (2009) described and analyzed the ethical reasoning ability of 70 baccalaureate nursing students and identified that the students showed an understanding of ethical reasoning and behavior, but not mastery of these skills. Nolan and Markert (2002) indicated that nursing students should be taught that there will be occasions where their personal code of ethics will conflict with practice. Nursing students need opportunities that facilitate development in moral and ethical reasoning.…”
Section: Introductionmentioning
confidence: 99%
“…[4] In addition to ethical problems involving health care professionals, issues relating to patient quality of life/death and dying, disagreement with a patient's behavior, and persons with HIV and other contagious diseases were also seen. [1,2,6] As these findings indicate, most of the ethical problems encountered by nursing students in clinical practice were related to unprofessional conduct disclosing and explaining information to patients, or, when described in the context of so-called principles of ethics, matters pertaining to patient autonomy, non-maleficence, and veracity.…”
Section: Introduction 11 Ethical Problems Encountered By Nursing Stumentioning
confidence: 99%
“…Etik ikilem tamamen tatmin edici bir alternatifin bulunmadığı, ne yapılırsa yapılsın, bazı ilke ve kurallar arasında çelişmenin olduğu durumlardır (13). Literatür incelendiğinde öğrencilerin klinik öğretimde yaşadıkları etik sorunların; yarar sağlama, zarar vermeme, gizlilik, mahremiyet, otonomi, gibi etik ilke ihlallerine temellendiği ve etik değerlerden en sık insan onurunun zedelendiği görülmektedir (3,7,9,11,14,15).…”
Section: Introductionunclassified